+0  
 
0
284
3
avatar

simplify the square root of 8 times the square root of 6 times the square root of 3.

Guest Feb 22, 2017
Sort: 

3+0 Answers

 #1
avatar+5541 
+1

\((\sqrt{8})(\sqrt{6})(\sqrt{3})\)

\(= \sqrt{(8)(6)(3)}\)

\(= \sqrt{(2)(2)(2)(2)(3)(3)}\)

\(= (\sqrt{(2)(2)})(\sqrt{(2)(2)})(\sqrt{(3)(3)})\)

\(= (2)(2)(3)\)

\(= 12\)

hectictar  Feb 22, 2017
 #2
avatar+10657 
0

Nice job hecticar....here is another way

sqrt 8  sqrt 6  sqrt 3  = sqrt(8*6*3) = sqrt(144) = 12

ElectricPavlov  Feb 22, 2017
 #3
avatar+5541 
+1

True...I was overthinking it a little haha.

hectictar  Feb 22, 2017

24 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details